The Gaze: Memory of Peeping in the Arabic Novel - Moshi, Lec.Dr. Sami Kareem (Thi Qar Arts Journal, 2023)
This research seeks to shed light on a philosophical term that has become one of the most prominent cognitive tools that the feminist theory has introduced in its approaches, and it re-examines the statements that the culture produced in its attempt to objectify the woman and draw her self-features, and her contribution to defining the roles that she practices according to a law that shapes it The dominant male powers are examining the woman and always putting her under surveillance.The law of surveillance, which most phenomenological philosophers talked about in their theses on the dialectic of self and other, altruism and ego identity, and the self that complies with a constant feeling of who is watching it, has received the attention of theorists in the feminist field, on the assumption that the woman is in a constant feeling of who is watching her and staring at her until she becomes an object that is viewed to her, and a self that contributed to its formation a group of selves outside it, and therefore it was necessary to review the reality of examining the cultural system that formed those powers and contributed to its formulation, from a series of promotional advertisements and films and theatrical works, to narrative texts There was something that established the correct convictions for the woman to be the one who stared at her and appeared before the audience and the viewer and the reader as she became a subject related to issues in the body, erotica, identity and femininity.From here, the research turned to presenting the term first, and to a critical approach that restores reading narrative productions as they present women from the perspective of man, staring at her and drawing her destiny that she must choose, and without a doubt she will be under the perspective of man and his dominant powers as she tries to get out of The predicament is to other patterned paths as well, and the man will be present in them and determine their social dimensions in advance.